Efficient Single-Photon Coupling from a Nitrogen-Vacancy Center Embedded in a Diamond Nanowire Utilizing an Optical Nanofiber. Issue 1 (December 2017) - Yonezu, Yuya; Wakui, Kentaro; Furusawa, Kentaro; Takeoka, Masahiro; Semba, Kouichi; Aoki, Takao
Abstract Nitrogen-Vacancy (NV) centers in diamond are promising solid-state quantum emitters that can be utilized for photonic quantum applications. Various diamond nanophotonic devices have been fabricated for efficient extraction of single photons emitted from NV centers to a single guided mode. However, for constructing scalable quantum networks, further efficient coupling of single photons to a guided mode of a single-mode fiber (SMF) is indispensable and a difficult challenge. Here, we propose a novel efficient hybrid system between an optical nanofiber and a cylindrical-structured diamond nanowire. The maximum coupling efficiency as high as 75% for the sum of both fiber ends is obtained by numerical simulations. The proposed hybrid system will provide a simple and efficient interface between solid-state quantum emitters and a SMF suitable for constructing scalable quantum networks.